Physical-mechanical evaluation of boards based on Pigüe Sawdust (Piptocoma discolor) and sugar cane bagasse in Pastaza - Gonzalez Rivera, Juan Elias (2018)
This study presents the evaluation of the physical-mechanical properties of vegetable fibers, which allows the use of Pigüecomer (Piptocoma discolor) sawdust and sugarcane bagasse (Saccharum officinarum) for the manufacture of agglomerated MDF boards, using two types of adhesive, white and paste. A completely randomized design was carried out, with six treatments and five repetitions in a total of 30 experimental units. The results showed that the best treatment was AE2 (50% sawdust, 50% cane bagasse and paste) with a moisture content of 9.36%, swelling 15.17%, moisture absorption 22.34%, maximum effort of tension 9.7 MPa, modulus of elasticity 19.2 MPa and maximum load 1836 N, which meets the standards established in the International Standards UNE-EN 322: 1994, UNE-EN 317: 1994, COVENIN 847-91 and ASTM D 1037 -1 2.